Possible utilization of silica gel sludge for the removal of phenol from aqueous solutions: Laboratory studies - Idris, Azni; Saed, Katayon (Springer Nature, 2003)
This paper discusses the adsorption capacity of silica gel sludge for phenol removal from aqueous solution. Kinetic experiments showed that phenol adsorption was completed after 2 h. Adsorption isotherms were measured for phenol from aqueous solution onto silica gel sludge under various pHs and temperatures. Results showed that the adsorption capacities for phenol was increased as pH decreased from 6.5 to 2. Temperature also was found to affect the adsorption isotherm. As temperature increases from 30 to 50°C, the adsorption capacity increases. The adsorption equilibrium of phenol on silica gel sludge was described by the linear Freundlich and Langmuir models. Furthermore, results showed that the isotherm parameters fit both linearized Langmuir and Freundlich adsorption isotherms. The Freundlich and Langmuir parameters at optimum pH was found as K f = 2.89, 1/n = 0.23 and K d = 22.0, q m = 7.98, respectively. Whereas, for those at optimum temperature it was observed as K f = 2.87, 1/n = 0.16 and K d = 20.93, q m = 7.91, respectively.